A SEM/EDS non invasive study of small portraits on copper support of the 17th and 18th centuries - Veiga, Alfredina; Mirão, José; Candeias, António José; Rodrigues, Paulo Simões; Martins Teixeira, Dora; Ginja Teixeira, Jorge (Cambridge Journals Online, 2015)
In this work we used the SEM/EDS technique in the morphological characterization and in-situ microanalysis of small portraits on copper support of the seventeenth/eighteenth centuries.
Keywords: SEM/EDS; microanalysis; portraits; miniatures; copper support; cultural heritage